RIRS with FV-UAS vs. ESWL for the management of 1–2 cm lower pole renal calculi in obese patients: a prospective study - Men, Chao; Xu, Miao; Zhang, Si-cong; Wang, Qing; Wu, Jie; Li, Yun-Peng (Frontiers in Medicine, 2024)
To evaluate the efficacy and safety of retrograde intrarenal surgery (RIRS) combined with fexible vacuum-assisted ureteral access sheath (FV-UAS) versus extracorporeal shock wave lithotripsy (ESWL) for the management of 1-2 cm lower pole renal calculi (LPC) in obese patients.This prospective, randomized study included 149 obese patients with 1-2 cm LPC. Patients were allocated into two groups: 76 patients underwent RIRS with FV-UAS, and 73 patients received ESWL.The parameters assessed included stone-free rate (SFR), retreatment rate, complications, operative time, and pain intensity measured by the Visual Analog Scale (VAS).Stone-free status was defined as the absence of stones on computed tomography or residual fragments smaller than 4 mm at 4 weeks post-procedure.The baseline characteristics of the two groups were comparable.The SFR was significantly higher in the RIRS group, reaching 86.8%, compared to 63.0% in the ESWL group (P = 0.034). Furthermore, the retreatment rate was significantly lower in the RIRS group, at 5.2%, versus 24.7% in the ESWL group (P < 0.001). The average operative time for RIRS was notably longer, at 65.3 ± 6.4 minutes, compared to 25.3 ± 7.8 minutes for ESWL (P < 0.001). The complication rates were 9.2% for the RIRS group and 6.8% for the ESWL group, with no statistically significant difference (P = 0.326). All complications were classified as Grade I or II according to the modified Clavien classification system. No significant differences were observed between the two groups regarding pain VAS scores and the composition of the stones. Conclusions RIRS with FV-UAS demonstrated superior efficacy, evidenced by a higher SFR and reduced retreatment rates compared to ESWL, despite a longer operative duration. Both treatment modalities showed comparable safety profiles. RIRS with FV-UAS emerges as a viable, effective, and reproducible intervention for managing 1-2 cm LPC in obese patients, providing significant clinical advantages.